Determinants of survival and growth of tree lucerne (Chamaecytisus palmensis) in the crop-livestock farming systems of the Ethiopian highlands - Mekonnen, Kindu; Jogo, W.; Bezabih, Melkamu; Mulema, Annet A.; Thorne, Peter J. (Springer, 2019)
The performance, expansion and contribution of tree lucerne has not reached to its full potential due to a number of factors. An action on-farm research was conducted with men and women farm households to (a) compare survival and growth of tree lucerne across contrasting sites and growing niches, and (b) identify the key determinants of tree lucerne survival and growth on farms in the crop-livestock systems. The research was conducted in eight research kebeles (the smallest administrative unit in the country) of the four Africa RISING (Africa Research in Sustainable Intensification for the Next Generation) project sites. Eight farmer research groups (FRGs) were formed in consultation with the group members. Each FRG consisted of 25–30 men and women farmers representing a range of social groups. Each farmer participating in the research received on average 50 seedlings. A total of 253 farmers participated in the research. After planting, data on survival, growth, root collar diameter and management were collected at 9 months using simple field monitoring tools. A total of ten sample plants were selected from the field of each farmer who planted tree lucerne, and these were labelled for continuous growth measurements. The on-farm research measurement was supplemented by cross-sectional survey data collected from a sample of FRG member households in the eight research kebeles. A combination of descriptive statistics, multivariate statistical techniques and econometric models were used for data analysis. The results of the study show that percentage survival on-farm were significantly higher for tree lucerne planted in backyards than those planted in outfields and for middle-resource class households. Household size, access to reliable water supply, and management factors—including fencing and watering planted-seedlings, mulching during dry periods, clean spot weeding and applying organic fertilizers—significantly enhanced survival and growth of tree lucerne in the planting sites.